THE CONCEPT OF LEGAL CERTAINTY REGULATION OF CSR PROVISION FOR THE WELFARE OF THE PEOPLE BASED ON LAW NUMBER 40 OF 2007 ON LIMITED LIABILITY COMPANIES - Rahman, Muhammad; Fahmi, Sudi; Bagio, Bagio (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
There is a legal vacuum related to the non-regulation of sanctions for companies that do not implement CSR/implement it but do not comply with legal provisions. Both in Law Number 40 of 2007 concerning Limited Liability Companies and regulations at the regional level. Such conditions mean that the realization of people's welfare as the goal of providing CSR cannot be fulfilled. The aim of this research is to analyze the concept of regulating legal certainty in providing CSR for the welfare of the people; To formulate the ideal concept of regulating legal certainty for providing CSR. This type of research is normative legal research. The approach used is a statutory, concept and case approach with qualitative analysis methods. The results of the research show that Firstly, the concept of regulating legal certainty for providing CSR for welfare based on Law Number 40 of 2007 concerning Limited Liability Companies does not provide legal certainty, as do the derivative regulations at the regional level, especially in Berau Regency, Kampar Regency, Semarang City, Kota Pematang Siantar and the Special Region of Yogyakarta, which have not yet explicitly regulated sanctions for companies that have not implemented CSR for the community or these companies have implemented CSR for the community but the implementation has not complied with the legal provisions governing CSR itself. The impact is that the provision of CSR by the company to the community around the company has not provided welfare for the community. Second, the ideal concept of regulating legal certainty in providing CSR for the welfare of the people based on Law Number 40 of 2007 concerning Limited Liability Companies, is the concept of regulating derivative regulations at the regional level, namely regulations as in Aceh Besar Regency Qanun Number 9 of 2019 concerning Social Responsibility and Company environment; as well as Siak Regency Regional Regulation Number 1 of 2013 concerning Corporate Social and Environmental Responsibility which regulates legal sanctions against companies that have not implemented CSR for the community or the company has implemented CSR for the community but the implementation has not complied with the legal provisions governing CSR itself. This ideal concept has demonstrated the success of implementing CSR for the community around the company so that people's welfare can be achieved through the CSR program..Keywords: CSR, People, Limited Liability Company.